2014
DOI: 10.1111/1471-0307.12123
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of ATPase activity in the acid tolerance of Lactobacillus rhamnosus strain GG

Abstract: This study examined the survival and acid stress response of nine lactic acid bacteria (LAB) including Lactobacillus rhamnosus strain GG in commercially available yoghurt products (low pH environment) during the long-term storage. Under the storage conditions investigated (52 weeks period at 5°C), there was a loss of the viability of Lactobacillus acidophilus, Lactobacillus casei and Bifidobacterium sp. within 35 weeks. However, L. rhamnosus strain GG, one of starter strains in a commercially available yoghurt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…L. rhamnosus GG has generally been recognized as safe (GRAS) status, often used to ferment dairy products such as yogurt or cheese (Bang et al, 2014; Galli et al., 2019). L. rhamnosus GG was reported to prevent gastrointestinal infections and diarrhea, stimulate the immune response, and prevent certain allergic symptoms (Segers & Lebeer, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…L. rhamnosus GG has generally been recognized as safe (GRAS) status, often used to ferment dairy products such as yogurt or cheese (Bang et al, 2014; Galli et al., 2019). L. rhamnosus GG was reported to prevent gastrointestinal infections and diarrhea, stimulate the immune response, and prevent certain allergic symptoms (Segers & Lebeer, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…LGG is a rod shaped, non-spore forming and facultative gram positive bacteria which is categorized as generally recognized as safe (GRAS) (Valík et al, 2008;Kailasapathy, 2014). Ot has been extensively studied and applied in dairy products such as cheese, milk and yogurt, with study on increasing the buttery flavoring compounds following different sugar substrate incorporation (Assaf et al, 2019;Bang et al, 2014;Jyoti et al, 2003). The health benefits of LGG includes the prevention or treatment of gastrointestinal infections and diarrhea, stimulating the immune responses and preventing certain allergic symptoms (Berni Canani et al, 2012;Fong et al, 2015;Segers & Lebeer 2014).…”
Section: Introductionmentioning
confidence: 99%
“…As a functional probiotic that has been extensively used in fermented foods and dietary supplements, LGG tolerates acid stress well and has several defense mechanisms to ensure its survivability. A previous study demonstrated the excellent acid tolerance ability of LGG, which had a high survival rate after 52 weeks of storage in yogurt (as a representative acidic fermented dairy products [1]. The mechanisms of acid resistance in lactic acid bacteria have been well documented, including the modulation of the proton-translocating ATPase to maintain the cytoplasmic pH homeostasis, the transition of pyruvate metabolism towards acetyl-CoA production, and the alteration of amino The LGG cells were labeled with fluorescein isothiocyanate (FITC) solution (1 mg/ml in 50 mmol/l sodium carbonate buffer, pH 8.9) before being administered to the mice.…”
Section: Discussionmentioning
confidence: 99%
“…Control, non-treated cells; pH 4.5, treated with pH 4.5 medium for 24 h; pH 7.0, treated with pH 7.0 medium. acid biosynthesis to supply energy for resisting acid stress [1,8,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation